Títulos de dívida corporativa de empresas brasileiras: investir em emissões do mercado interno ou externo? - Nunes, Ricardo Machado (2014)
The objective of this study is to analyze the yield difference between corporate debt issuance of Brazilian companies in local and foreign markets. From the perspective of the investor, we attempt to answer whether, once we control for risks, it is better, on average, to acquire a local (debenture) or external (bond) security from the same issuer. To this end, we examine 177 local and 119 international bond issues of 31 Brazilian non-financial companies from January 2004 to April 2013. Panel regressions with fixed effects to control for the issuer’s characteristics shown that, on average, the external market bond yields 164 to 197 bps more than the local debentures, and that this difference is statistically significant. This difference is due to greater availability and variety of corporate bonds in the foreign market, to the existence of a captive demand from institutional investors for bonds in the local market and to the lack of integration between markets. We also identify the participation of individuals in the foreign market as a relevant factor, as well as the higher debt structuring costs charged by investment banks in the domestic market. In turn, the lack of investors’ awareness and operational barriers, such as transaction costs, impossibility of trading in the international market and of short selling in local market, limit the arbitrage. The latter also causes overpricing of the local market bonds for only the views of the most optimistic investors are reflected in prices. The local institutional investors’ high sensitivity to returns volatility also appears relevant.